1997
DOI: 10.1079/bjn19970029
|View full text |Cite
|
Sign up to set email alerts
|

Secretion and reabsorption of endogenous protein along the small intestine of sheep: estimates derived from15N dilution of plasma non-protein-N

Abstract: Sheep fitted with a PVC cannula in the dorsal rumen, a silastic infusion tube in the abomasum, and single 'T'-shape PVC cannulas in the proximal duodenum @I), distal duodenum (D2), mid-jejunum (J), and terminal ileum (I), were fed on diets varying in crude protein (Nx6.25) and fibre contents. Reducing the environmental burden of livestock production systems is a major objective for current nutrition research. To achieve this objective the first option is to replace the external inputs of concentrate feeds and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
39
3
1

Year Published

1999
1999
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(48 citation statements)
references
References 17 publications
5
39
3
1
Order By: Relevance
“…The above reabsorption values are considerably higher than those observed by Voigt et al (1996) and Van Bruchem et al (1997) for protein N in the intestinal section between the duodenum and the ileum. These authors found average values of 50%).…”
Section: Discussioncontrasting
confidence: 50%
See 3 more Smart Citations
“…The above reabsorption values are considerably higher than those observed by Voigt et al (1996) and Van Bruchem et al (1997) for protein N in the intestinal section between the duodenum and the ileum. These authors found average values of 50%).…”
Section: Discussioncontrasting
confidence: 50%
“…Kay (1969) also determined a similar N secretion (7 g/d) using isolated intestinal loops of sheep. In mul-tiply fistulated nearly adult sheep Voigt et al (1996) and Van Bruchem et al (1997) found higher secretion of protein-N (14 and 17 g/d). As to the metabolic weight the mean value of our study (0.67 g N/kg BM°7 5 ) was identical with that reported by Voigt et al (1996) and only somewhat lower than the results of Van Bruchem et al (1997) (0.83 g N/kg BW 0 75 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Endogenous protein secretions, plus associated losses, are an important feature of digestive tract metabolism in both ruminants (e.g., van Bruchem et al, 1997;Ouellet et al, 2002) and non-ruminants (e.g., de Lange et al, 1990;Hess et al, 1998). Various methodological and conceptual approaches have been used to quantify such secretions but the majority have considered the digestive tract as a single unit (e.g., de Lange et al, 1990), rather than a series of linked and interacting units (e.g., van Bruchem et al, 1997;Ouellet et al, 2002).…”
Section: Introductionmentioning
confidence: 99%